Energy of a single electron in gaseous media: Related Topics - Shikin, V.B.; Nazin, S.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The so-called «optical» approximation in the theory of electron energy spectrum in the presence of scattering centers with positive scattering length randomly distributed with the average density ng is considered for a number of inert gases. The average minimal energy W of a single electron calculated beyond the optical approximation reveals a behavior qualitatively different from that of the same quantity W0 derived within the optical approximation. Results of calculations are in qualitative agreement with experimental data available for the W(ng)dependence for different cryogenic gases.